Vision modulation, plasticity and restoration using non-invasive brain stimulation – An IFCN-sponsored review. Issue 4 (April 2020) - Sabel, Bernhard A.; Thut, Gregor; Haueisen, Jens; Henrich-Noack, Petra; Herrmann, Christoph S.; Hunold, Alexander; Kammer, Thomas; Matteo, Barbara; Sergeeva, Elena G.; Waleszczyk, Wioletta; Antal, Andrea
Highlights: Normal/abnormal vision can be modulated by non-invasive stimulation beyond the stimulation period. Clinical impact on plasticity and restoration in patients with low vision is critically evaluated. Challenges are discussed in the field of transcranial/extracranial stimulation of the eye and brain. Abstract: The visual system has one of the most complex structures of all sensory systems and is perhaps the most important sense for everyday life. Its functional organization was extensively studied for decades in animal and humans, for example by correlating circumscribed anatomical lesions in patients with the resulting visual dysfunction. During the past two decades, significant achievements were accomplished in characterizing and modulating visual information processing using non-invasive stimulation techniques of the normal and damaged human eye and brain. Techniques include transcranial magnetic stimulation (TMS) and low intensity electric stimulation using either direct or alternating currents applied transcranially (tDCS or tACS) near or above the visual cortex, or alternating currents applied transorbitally (trACS). In the case of transorbital stimulation of the visual system the electrodes are attached near the eye, to the eyelids (transpalpebral electrical stimulation – TPES) or the cornea (tanscorneal electrical stimulation TcES). Here, we summarize the state-of-the-art of visual system magnetic and electric stimulation as a method to modulate normal vision, induce brain plasticity, and to restore visual functions in patients. We review this field's history, models of current flow paths in the eye and brain, neurophysiological principles (e.g. entrainment and after-effects), the effects on vision in normal subjects and the clinical impact on plasticity and vision restoration in patients with low vision, with a particular focus on "off-line" or "after-effects". With regard to the therapeutic possibilities, ACS was demonstrated to be effective in patients affected by glaucoma and optic neuropathy, while tDCS and random noise stimulation (tRNS) are most promising for the treatment of amblyopia, hemianopia and myopia. In addition, rTMS applied above the occipital area is a promising approach to treat migraine, neglect and hemianopia. Although the response to these treatment options is better than to sham stimulation in double blinded clinical studies, the clinical efficacy is still rather variable and a proportion of patients do not respond. It is therefore imperative to better understand the mechanisms of action to be able to optimize treatment protocols possibly through personalization of brain stimulation protocols. By identifying the current opportunities and challenges in the field, we hope to provide insights to help improve neuromodulation protocols to restore visual function in patients with visual system damage.